Digitalization and Artificial Intelligence: Is it the future of mental healthcare in Pakistan? - Imran, Nazish; Haider, Imran Ijaz (Journal of Pakistan Psychiatric Society, 2022)
Mental health problems are increasingly being recognised as a major public health concern among the leading causes of disease burden globally. Recent report suggests that in Pakistan, over 15 million people are suffering from some form of mental illness.“Digital mental health” is defined as any application of digital health technology for mental health assessment, support, prevention, and treatment, whereas Artificial intelligence (AI) is “the science and engineering of making intelligent machines”.